Envelhecimento ativo de professores de um programa de atividades físicas da UnATI/ESALQ/USP - Moraes, Paulo Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Active aging is a process that focuses on the quality of life of elderly, as proposed by WHO and Brazilian official documents. There is a break with the world of work with retirement, and increased leisure time. Studies indicate adherence to physical activity at this stage, enabling active aging. Knowing that regular physical activity is associated with several health benefits and functional capacity, this study aimed to understand the active aging process of the group of individuals who participate in a physical activity program UnATI/ ESALQ-USP, especially of retired teachers, featuring the group regarding: 1- overall functional fitness index (OFFI); 2- level of physical activity; 3- quality of life (in three domains: physical functioning, role limitations due to physical health and vitality); 4- physical activity in the retirement of teachers group. Functional fitness (OFFI) was evaluated by the battery of tests AAHPERD; the level of physical activity was assessed by the IPAQ long version and the quality of life using the SF-36 questionnaire - Short Form, the results were analyzed with nonparametric statistics through U of Mann Whitney test and correlated statistically by Spearman. Also exercise classes were observed and there was realized interviews about the relationship between physical activity and retirement teachers. 160 individuals in program ESALQ of physical activity (0.4% of elderly population of Piracicaba), 47 subjects volunteered for the study, 18 teachers, who signed a consent form. We evaluated age, weight, height and BMI, with the 95%. Retired teachers represented 38% of sample when it is compared to each other professions of the other participants (N = 47). In an interview, teachers (89%) said that they did not perform physical activity before retirement, so UnATI- ESALQ program contributes to activity in elderly. Although most participants (46.94%) of the group studied was classified as weak or very weak when OFFI was...

O envelhecimento ativo é um processo que visa a qualidade de vida do idoso, conforme proposto pela OMS e em documentos oficiais brasileiros. Com a aposentadoria, há uma ruptura com o mundo do trabalho e maior tempo livre. Estudos indicam adesão à atividade física nesta fase, possibilitando o envelhecimento ativo. Sabendo que a prática de atividade física regular está relacionada a vários benefícios à saúde e à capacidade funcional, este estudo teve como objetivo compreender o processo de envelhecimento ativo do grupo de indivíduos participantes de um programa de atividade física da UnATI/ESALQ-USP, especialmente dos professores aposentados, caracterizando o grupo em relação: 1- ao índice de Aptidão Funcional Geral (IAFG); 2- ao nível de atividade física; 3- à qualidade de vida (em três domínios: capacidade funcional, limitação por aspectos físicos e vitalidade); 4- à atividade física na aposentadoria dos professores do grupo. O IAFG foi avaliado pela bateria de testes da AAHPERD; o nível de atividade física foi avaliado pelo questionário IPAQ versão longa e a qualidade de vida pelo questionário SF-36 - Short Form, cujos resultados foram analisados com estatística não paramétrica por meio do teste U de Mann Whitney e correlacionados estatisticamente por Spearman. Também foram observadas aulas de ginástica e realizadas entrevistas sobre a relação atividade física e aposentadoria entre os professores. Dos 160 idosos do programa de atividades físicas da ESALQ (0,4% da população de idosos de Piracicaba), 47 indivíduos se voluntariaram para a pesquisa, sendo 18 professores, os quais assinaram Termo de Consentimento Livre e Esclarecido. Avaliou-se idade, peso, estatura e IMC, com de confiança de 95%. Os professores aposentados representaram 38% da amostra em comparação com cada uma das outras profissões dos outros participantes (N=47), os quais (89%), em entrevista, afirmaram não realizar atividade...
Keywords: Physical education and trainig; Educação fisica; Envelhecimento; Professores - Aposentadoria; Aptidão física; Qualidade de vida; Exercícios físicos para idosos; Professores aposentados - Piracicaba (SP); Escola Superior de Agricultura Luiz de Queiroz